ANALISIS FAKTOR BERPENGARUH TERHADAP NON PERFORMING FINANCING (NPF) PERBANKAN SYARIAH DI INDONESIA - Pani Akhiruddin Siregar; Evi Flora Harianta Sirait; Kadri Bancin (Jurnal At-Tabayyun, 2019)
This research aims to analyze deeply the influence of Money Supply, BI Rate, CAR and FDR to NPF Sharia Banking Indonesia. Quantitative data types in the form of monthly time-series data From The Financial Ratio Report of Sharia Commercial Bank and Sharia Business Unit published by Sharia Banking Directorate, Bank Indonesia and the Bank Licensing and Banking Information Department, Indonesia Financial Services Authority through Sharia Banking Statistics Bank Indonesia/Indonesia Financial Services Authority from January 2006 to January 2018. The results showed: (1) A regression model on the independent variable simultaneously affects the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (2) Money supply variable influential positive and significant to NPF variable; BI Rate variable influential negative and insignificant to NPF variable; CAR and FDR variable has no influential positive and insignificant to NPF variable.